3D residual stress modelling of welded high strength steel plate-to-plate joints - Lee, Chi King (2014)
A numerical investigation on the residual stress distributions near the weld toe of plate-to-plate Y-joints fabricated by using high strength steel (HSS) plate is carried out in this study. A fully 3D sequentially coupled thermal-mechanical modelling procedure is employed for residual stress analysis for the HSS plate-to-plate joints. Two specimens respectively fabricated by welding at ambient temperature and at a preheating temperature of 100°C are investigated. The 3D numerical models reveal that while high tensile transverse residual stress, which is perpendicular to the weld, is generated near the weld toe of the joint middle section, proper preheating could significantly reduce the magnitude of the residual stress. In addition, it is found that the welding direction between successive weld pass could also affect the maximum residual stress value near the chord weld toe.